Approximation to the economic cost of healthcare for hypertensive patients diagnosed with COVID-19 - Jesús Calderón-Moreno; María Jesús Delgado-Rodriguez; Raúl Juárez-Vela; Raúl Juárez-Vela; Clara Isabel Tejada-Garrido; Regina Ruiz de Viñaspre-Hernández; Regina Ruiz de Viñaspre-Hernández; Amaya Burgos-Esteban; Pilar Sánchez-Conde; Pilar Sánchez-Conde; Vicente Andreu-Fernández; Vicente Gea-Caballero; et al. (Frontiers Media S.A., 2024)
IntroductionMany researchers have focused their studies on hypertension due to its over-representation among COVID-19 patients. Both retrospective and observational studies conducted close to the Wuhan area have reported that hypertension is the most common comorbidity observed in patients affected by COVID-19.ObjectiveOur objective is that patients with arterial hypertension have a worse prognosis in terms of evolution leading to higher costs.MethodsA retrospective cross-sectional study was conducted. A total of 3,581 patients from La Paz University Hospital (LPUH) during the period between 15 July 2020 and 31 July 2020 were included in this study.ResultsIt should be noted that 40.71% of the patients were hypertensive. As expected, hypertension was associated with men, among whom we observed a higher prevalence and a higher age (median age of 77 years (IQI: 65-85) versus 52 years (IQI: 37-64), p-value < 0.001). Hypertensive patients had a higher prevalence of dyspnea (52.14% vs. 47.15%, p-value = 0.004) and altered awareness (14.89% vs. 4.30%, p-value <0.001). The non-parametric Kaplan-Meier curve estimates the survival of patients in the two study groups. We can see how patients with hypertension have a higher associated mortality, with the difference being statistically significant, p-value (log-rank) = 0.004. Only for the appearance of complications during hospitalization, the group of hypertensive patients reached the figure of €1,355,901.71 compared to the total of 421,403.48 € for normotensive patients.ConclusionOur study shows the worse clinical evolution of patients with COVID-19 in terms of associated morbidity and mortality. It also shows that the cost of managing patients with hypertension is greater than that of managing normotensive patients.